Pelvic Pain in Men with Mycoplasma Genitalium - Yumi Seo (Urogenital Tract Infection, 2024)
Purpose There are debates about Mycoplasma genitalium (M. genitalium) causing prostate infection and inducing pelvic pains. Consequently, M. genita-lium-asso-ciated pelvic pains were characterized and their manifestation in male pelvic pain syndrome (MPPS) was evaluated through a case-control study. Materials and Methods The presence of M. genitalium-associated pelvic pains was examined in 113 M. genitalium-infected men, and the typical presentations of mycoplasma-associated MPPS were characterized through a case-control study involving 80 mycoplasma-infected and 234 case-matched uninfected controls. Finally, changes in symptoms following antimicrobial treatments were compared between 27 cured and 14 persistently infected cases. Results Pain locations from 113 men were followed as items-1a for 25.7%, 1b for 21.2%, 1c for 31%, 1d for 18.6%, 2a for 59.3%, and 2b for 23% from the Korean National Institutes of Health-Chronic Prostatitis Symptom Index (NIH-CPSI) questionnaire. In addition, the sum scores from the pain domain, voiding domain and total score were 6.68±4.75, 2.69±2.66, and 15.00±8.66, respectively. Successful antibiotic therapy significantly reduced the total score from baseline (15.148±6.798 vs. 5.357±7.025, p=0.001). From the case-control study, mycoplasma-infected men had pains more frequently during urination (1c) and on the tip of the penis (2a) (all p=0.0001) than the controls. Conclusions It was found that M. genitalium infection is associated with clinically significant male pelvic pains, which improved with adequate antimicrobial therapies. Urethral irritation symptoms without pyuria may be the typical characteristics of mycoplasma-associated pelvic pains in MPPS.